2016
DOI: 10.1002/cmdc.201600129
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for Differential Recognition of G‐Quadruplex versus Double‐Helix DNA by Bis‐Phenanthroline Metal Complexes

Abstract: 1,10-Phenanthroline (Phen) derivatives are attractive ligands to provide metal complexes that are selective for different DNA secondary structures. Herein, we analyze the binding processes of two bis-Phen analogues and their Ni(II) complexes toward double-stranded DNA and telomeric G-quadruplex DNA by calorimetric and spectroscopic techniques. The free ligands can adapt to both DNA arrangements. Conversely, metal ion coordination produces an increase in ligand affinity for the tetrahelical structure, whereas i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…The ICD spectral features at pH 5.5 and 7.4 well overlap one to each other when normalized on the ligand concentration (Fig. S9C) and significantly resemble those previously reported for 042 in the presence of ctDNA or human telomeric G-quadruplex at low ionic strength 33 . S1 footprinting performed at pH 5.5 confirmed a different behaviour of the metal complex vs the free ligand.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The ICD spectral features at pH 5.5 and 7.4 well overlap one to each other when normalized on the ligand concentration (Fig. S9C) and significantly resemble those previously reported for 042 in the presence of ctDNA or human telomeric G-quadruplex at low ionic strength 33 . S1 footprinting performed at pH 5.5 confirmed a different behaviour of the metal complex vs the free ligand.…”
Section: Resultssupporting
confidence: 84%
“…The use of some Phen derivatives as hit for this evaluation provided stimulating hints. We previously showed that G4 structures are preferentially recognized by systems comprising two Phen units organized around one coordinated metal ion according to a planar geometry 31,33 . Taking into account the reduced available surface area of the C-C + pair in comparison to the G4 tetrads, we expected that only one aromatic moiety should be sufficient to target an iM through stacking interactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the great variety of aromatic heterocycles that have been demonstrated interesting properties as potential quadruplex ligands, the 1,10-phenanthroline heterocyclic system deserves a mention. Several derivatives have been found to bind to quadruplexes with good affinity and selectivity, both in the form of organic ligands [ 35 , 36 , 37 , 38 ] or as metallo-organic derivatives [ 35 , 39 , 40 , 41 , 42 ]…”
Section: Introductionmentioning
confidence: 99%
“…Among the great variety of aromatic heterocycles that have been demonstrated interesting properties as potential quadruplex ligands, the 1,10-phenanthroline heterocyclic system deserves a mention. Several derivatives have been found to bind to quadruplexes with good affinity and selectivity, both in the form of organic ligands [35][36][37][38] or as metalloorganic derivatives [35,[39][40][41][42] On the other hand, natural and synthetic guanidine derivatives have been of great interest due to their pronounced biological activity [43]. Among their properties, it is worth mentioning their use in neurodegenerative disorders as anti-inflammatory agents, as inhibitors of the Na + /H + exchanger and blockers of the epithelial sodium channel, as inhibitors of F1F0-ATPase, as cardiovascular and as antidiabetic or chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%